Temperature dependence of the superconducting giant-vortex state. Theory and Experiment - de la Cruz, F.; Fink, H.J.; Luzuriaga, J. (American Physical Society, 1979)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina